2020
DOI: 10.1002/acn3.51006
|View full text |Cite
|
Sign up to set email alerts
|

Early life metal dysregulation in amyotrophic lateral sclerosis

Abstract: ObjectiveDeficiencies and excess of essential elements and toxic metals are implicated in amyotrophic lateral sclerosis (ALS), but the age when metal dysregulation appears remains unknown. This study aims to determine whether metal uptake is dysregulated during childhood in individuals eventually diagnosed with ALS.MethodsLaser ablation‐inductively coupled plasma‐mass spectrometry was used to obtain time series data of metal uptake using biomarkers in teeth from autopsies or dental extractions of ALS (n = 36) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 45 publications
2
23
0
Order By: Relevance
“…Studies of their growth and composition play an especially important role in our understanding of ancient human behavior, development, and evolution. [1][2][3][4] Teeth also serve as important records of toxic environmental exposures in living people, [5][6][7][8] perhaps best exemplified by the detection of radiogenic elements in American children following atomic testing in the 1950s. [9,10] In this unprecedented situation, a "Baby Tooth Survey" was launched to assess the amount of a radioactive variant of strontium in children born in St. Louis, Missouri before, during, and after a period of especially heavy nuclear testing in 1953.…”
Section: Introduction Tooth Growth and Mineralization: A Microscopic Archive Of Developmental Informationmentioning
confidence: 99%
“…Studies of their growth and composition play an especially important role in our understanding of ancient human behavior, development, and evolution. [1][2][3][4] Teeth also serve as important records of toxic environmental exposures in living people, [5][6][7][8] perhaps best exemplified by the detection of radiogenic elements in American children following atomic testing in the 1950s. [9,10] In this unprecedented situation, a "Baby Tooth Survey" was launched to assess the amount of a radioactive variant of strontium in children born in St. Louis, Missouri before, during, and after a period of especially heavy nuclear testing in 1953.…”
Section: Introduction Tooth Growth and Mineralization: A Microscopic Archive Of Developmental Informationmentioning
confidence: 99%
“…Our analysis of five pollutants observed weekly throughout pregnancy and birth weight is the first analysis to identify critical windows to a mixture observed at high-temporal resolution within a distributed lag mixture model framework. Previous studies have either estimated critical windows for a mixture observed at high temporal resolution in an additive DLM setting (Figueroa-Romero et al, 2020;Horton et al, 2018) or to a mixture observed at one or a small number of time points (Levin-Schwartz et al, 2019;Chiu et al, 2018;Valeri et al, 2017). Given the sequential nature of fetal development, where changes occur over varying time scales ranging from many months down to a few days, data driven methods that allow for high resolution and precision in identifying critical windows due to environmental mixtures have the potential to open doors to discovery and understanding in biological science (Wright, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Using the copper complex CuATSM, a safe vehicle of copper selective in cells with damaged mitochondria, they demonstrated that early CuATSM treatment of pups expressing SODG93A with CCS avoided the early mortality and allowed a normal grow [ 118 ]. According to this study, direct evidence reveals that altered metal uptake during specific early lifetime windows is associated with adult-onset ALS [ 85 ]. Thus, copper homeostasis is undeniably crucial in the maintenance and function of motor neurons, and therefore in the pathogenic mechanisms underlying motoneuron degeneration.…”
Section: Current Insight Into the Potential Of Regenerative Medicine ...mentioning
confidence: 99%